PENGEMBANGAN ORGANISASI DALAM PERILAKU ORGANISASI - Devi Fazilatun Nisa; Gading Putri Pratiwi; Khaerul Nur Pratiwi; Sunarti; Hasanah (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This scientific work with the theme "Organizational Development in Organizational Behavior" is a paper not the result of research but the result of a literature study. In this case, the author can collect data through the media literature. According to (Wijaya, 2017), argues that organizational behavior is a scientific discipline that studies individual behavior in organizations and its impact on individual, group or organizational performance. The goals of organizational development in general are to build company capacity in solving problems, adapting to change, having high competitiveness, increasing achievement and effectiveness overall work of all groups, departments and organizations as well as creating organizational health, forming effective changes and increasing engagement with organizational goals.According to (Gibson, 1985), there are three methods used in organizational development.The results of organizational development are systems teaching and learning and information systems & technology. Organizational development has implications for organizational capability in making quality decisions by making changes to structure, culture, technology, human resources and so on through irrational processes and is carried out to make efforts to correct various failures and mistakes, as well as to meet various expectations that are desired, as well as part of how to improve the quality and quantity that was previously owned, by maintaining the basic and main values contained in the organizational culture.